Development and Validation of UV-spectrophotometric Method for the Estimation of Wintergreen Oil in Pharmaceutical Formulation - Deepali; Joshi, Vijaya G; Ramachandra Setty, S; Geetha, M (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: The study aimed to develop and validate a simple UV-spectrophotometric method for quantifying Wintergreen oil in micro/nanosponges. Materials and Methods: The method was developed using acetonitrile as a solvent system and validated for various parameters such as linearity, precision, repeatability, the Limit of Detection (LOD), and the Limit of Quantification (LOQ), and accuracy according to ICH guidelines. Results: The oil showed an absorption maximum at 237nm. Linearity between concentration and absorbance was established within a concentration range of 2 to 28 mcg/mL and showed a regression coefficient of 0.9746. The recovery of 97.14-107.82% and % RSD of less than 2% for repeatability, intraday, inter-day, and ruggedness revealed that the method is accurate and precise. The LOD and LOQ were determined as 0.103 mcg/mL and 0.312 mcg/mL respectively. Insignificant changes in absorption values with deliberate variation in absorption maximum indicate the method's robustness. The entrapment efficiency and loading capacity ranged between 88-97.82% and 3.085-24.35%. Conclusion: The validation results conclude that the method is simple, sensitive, precise, accurate, and robust. Hence, the method was used for quantifying wintergreen oil in micro/nanosponges. The procedure can further be adapted for analysing wintergreen oil in other pharmaceutical preparations and commercial products.
Keywords: Wintergreen oil; UV-spectrophotometry; Validation; Micro/nanosponges; Pharmaceutical formulation